Strengthening Student Discipline through Digital Record-Keeping: A School Action Research at SMP IT al-Amanah - Abdul Muhyi, Ujang (AIM: Journal of Islamic Education Management, 2023)
Schools, as educational entities, bear the responsibility for the process of cultivating students' disciplined character. Therefore, the character of discipline is not solely rooted and nurtured within the dimensions of individual humans but also collectively within educational entities or institutions. The primary objective of this research is to evaluate the enhancement of discipline within the school environment using the Attitude Record approach as an analytical tool. The method employed in this study is the School Action Research (SAR) approach. The research findings reveal that implementing the Attitude Record as a tool for recording and analyzing student behavior data yields significant benefits in enhancing discipline within the school. The Attitude Record enables school management to conduct more precise evaluations of disciplinary situations, identify student behavioral patterns, and formulate actions that align with the existing conditions. Schools can take practical and targeted measures to improve discipline comprehensively through this approach.The implications of these findings extend not only to the relevant school environment but also to offer guidance for other educational institutions. The utilization of similar applications to manage student behavioral data holds the potential to elevate discipline across various educational establishments. The case analyzed in this research, specifically at SMPÂ  IT Al-Amanah, is a valuable example for other institutions to adopt a similar approach to enhance student discipline